Correlation between Students' Motivation and Listening Ability by Using American English Podcasts on Spotify for XI Grade Students of SMA Negeri 2 Mranggen in the Academic Year 2024/2025 - Firdausy, Syahda Erinna; Ambarini, Ririn; Lestari, Siti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Listening is one of the important factors in mastering English. Teaching listening to students is also not an easy task. It requires high student motivation to want to learn listening. This research aims to explore the potential impact of motivation on the development of listening skills in students. This research also delves into how motivational factors influence the effectiveness of using American English podcasts as a learning tool. The researcher conducted a research to test students' listening ability using a podcast. This research using pre-experimental design. To collect data, the researcher used a questionnaire and a listening test as instruments. In this research, 35 students from one class at SMA Negeri 2 Mranggen were used as the sample. The researcher used total sampling as the sampling technique. To analyze the questionnaire data, the researcher used categories ranging from very poor, poor, average, good, to very good. Meanwhile, to test the pre-test and post-test data, the researcher used paired sample t-test. After analyzing and testing the obtained data, it can be concluded that there is a correlation between students' learning motivation and their listening ability. Because the students' learning motivation is said to be quite high, there is an increase in their post-test scores after receiving treatment from the researcher